Study of Yoga Intervention on Hemoglobin, Blood Sugar, Complete Blood Count, and Differential Leukocyte Count Levels in Indo-Tibetan Border Police Personnel for High-Altitude Missions in India - Arya, Jaideep; Sharma, Sunil; Duhan, Ishwar Singh; Chander, Harish; Priyanka; Jaspreet (International Research Journal of Ayurveda & Yoga, 2024)
Background: High-altitude (HA) environments pose significant physiological challenges to the human body, including hypoxia, cold exposure, and increased physical demands. These conditions can lead to fluctuations in vital health parameters such as hemoglobin, blood sugar, and immune function. Yogic practices, including Āsanas (physical postures), Prāṇāyāma (breathing techniques), and meditation, have been shown to improve cardiovascular, immune, and metabolic functions. Aim: This study investigates the physiological effects of structured Yogic practices on Indo-Tibetan Border Police (ITBP) personnel stationed in HA regions, with a focus on hemoglobin, blood sugar, complete blood count (CBC), and differential leukocyte count (DLC). Materials and Methods: A randomized case–control design was employed, involving 100 ITBP personnel. Participants were divided into a control group following regular physical activities and an intervention group practicing a comprehensive Yogic regimen for 8 weeks. Pre- and post-intervention measurements of hemoglobin, blood sugar, CBC, and DLC were taken. Statistical analysis was conducted using paired t-tests. Intervention: The intervention group engaged in structured Yogic practices, including Āsanas, Prāṇāyāma, and meditation, over an 8-week period. The control group maintained their regular physical activities without additional Yogic practices. Results: The intervention group exhibited significant improvements in key physiological parameters. Hemoglobin levels increased from 12.237 g/dL to 13.103 g/dL, while fasting blood sugar levels decreased from 88.453 mg/dL to 85.056 mg/dL. Total leukocyte count improved from 6789.43 to 6977.04 cells/∝L, and neutrophil levels rose from 7163.10 to 7388.04 per mm³, reflecting enhanced immune function. Conclusion: This study demonstrates that specific Yogic practices positively impact hemoglobin levels, blood sugar regulation, and immune function. The findings suggest that Yoga can promote health and operational readiness among personnel in HA environments, highlighting the value of incorporating Yoga into the routines of individuals exposed to extreme physical and mental conditions, such as ITBP personnel.